Influencing Factors on Vehicles Lateral Stability on Tunnel Section in Mountainous Expressway under Strong Wind: A Case of Xi-Han Highway - Lu Wang; Xiaoxin Chen; Hong Chen (Advances in Civil Engineering)
When a car is running at high speed, the canyon wind at the bridge-tunnel junction in the mountainous area brings along the acceleration effect. The aerodynamic lateral force will cause the vehicle sideslip and unsteady steering, which is extremely harmful to driving safety. In this paper, Xi-Han Expressway is taken as the research object to analyze the influencing factors of vehicle’s lateral stability by combining the theoretical research of the finite element method, automobile aerodynamics, and speed limit with field investigation and simulation test. CarSim software is used for simulation to explore the influence of different positions of the circular curve on vehicle lateral stability. The results show that the wind level affects the tunnel exit’s unfavorable section on the circular curve. The larger the wind level, the larger the proportion of the tunnel exit’s unfavorable section on the circular curve. The proportions of tunnel exit’s unfavorable section on the circular curve under 6–9 wind levels are 33.33%, 38.89%, 55.56%, and 66.67%, respectively. In addition, the lateral stability of vehicles under level 6–8 wind scale is the worst when the tunnel exit is located at 5° position on the circular curve. The results indicate the influence of strong wind on the lateral stability of vehicles in mountainous expressway. The research can optimize the design of the highway tunnel group and provide the basic theory and method basis for the quantitative management and scientific management of the road traffic management department.